RESOLUSI KONFLIK PASCA PEMILIHAN KEPALA WEDEROK MELALUI MODAL SOSIAL - Kolne, Salesius Vitalis; Atanus, Fidelis; Kehik, Bernardus Seran (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2018)
The post-Pilkades conflict in Wederok Village, Weliman Sub-District, Malaka Regency is still ongoing. conflict resolution through formal institutions leaves a new problem. The purpose of this study is to offer a social capital-based conflict resolution. The research method used is descriptive. The results of the study indicate that the mediation efforts undertaken have not touched the essence of the source of conflict. The recommended conflict resolution effort is the Deliberative conflict resolution model "Maun-Alin". The purpose of this concept is to resolve the conflict by using the Deliberative model, where every citizen without the intervention of the government or customary institutions conveys the contents of his conscience, through the spirit of public space discourse.